EDUCATION POLICY ANALYSIS IN ORDER TO IMPROVE TEACHER PROFESSIONALISM - Nuraeni Nuraeni; I Wayan Widiana; I Gede Ratnaya (Jurnal Syntax Transformation, 2023)
Teacher professionalism can be seen from its role in carrying out tasks, namely developing the potential of students with heterogeneous backgrounds, both basic abilities, social, economic and cultural. Today's teacher professionalism is still included in the "semi" or "quasi" professional category because their work, such as teaching, is not fully given autonomy rights in practice. Professionalism in relation to the right to autonomy for a teacher in carrying out his main duties as an educator and teacher includes the ability to plan, implement and evaluate learning. Meanwhile, without mastering various basic knowledge about science, about students, about the society and culture in which the school operates, learning theory, various learning models, and various evaluation models, it is difficult for teachers to easily adapt to the new demands of implementing national education keep changing. As for achieving the real category of teacher professionalism, teacher positions must require further education and special training, namely at least having a Bachelor's degree and continuing with specialized education in their field which currently can be pursued in teacher professional education (PPG).